WORK MOTIVATION OF ADMINISTRATION STAFF IN ISLAMIC HIGHER EDUCATION: A CASE STUDY AT UNIVERSITY OF DARUSSALAM GONTOR - ahmad fauzan kamal; Yayan Firmansyah (Islamic Business and Management Journal, 2022)
Study on work motivation predominantly conducted on its effect on various employee attitude and behavior, and rarely explore the content of work motivation itself. Particularly in higher education, study on it mostly focused on academic staff. Thus, this study aims to explore the work motivations of administration staff, particularly in Islamic higher education, as well as Islamic view on such motivations. In doing so, qualitative approach was used and focusing on temporary adiminstration staff. In this research, totally eight interviews were conducted with five temporary administration staff, two heads of divisions, and one head of Human Resource Department. The results of this study indicate that Work motivation of administration staff is varied, ranging from showing gratitude, helping the institution, seeking blessing, inner calling, getting experiences, getting networking, obligation to serve, to prepare for further study. Further, all the motivations have been found to be related to the teachings of Islam. It has been detected that the work motivation that they belong to is the practice of what they have learned from the Qur'an and Hadith.